Cover Image. Issue 2 (26th January 2018) - Camus, G.; Han, B.; Asselah, T.; Hsieh, D.; Dvory‐Sobol, H.; Lu, J.; Svarovskaia, E.; Martin, R.; Parhy, B.; Miller, M. D.; Brainard, D. M.; Kersey, K.; et al.
Abstract : The cover image, by Gregory Camus et al., is based on the Original Article Resistance characterization of ledipasvir and velpatasvir in hepatitis C virus genotype 4, DOI:10.1111/jvh.12795 .